The Comparative Effects of Listening to Prayer Recitation and Music Therapy Intraoperatively on Postoperative Pain - Rahman, Farah Syaza; Yahya, Nurlia; Md Din, Nor Mohammad; Izaham, Azarinah; Wan Mat, Wan Rahiza (IIUM Medical Journal Malaysia, 2020)
Introduction: Non-pharmacological interventions are considered as successful adjuncts to manage pain. We are studying the comparative effects of listening to prayer recitation and music therapy intraoperatively as non-pharmacological interventions on postoperative pain and intraoperative haemodynamics. Materials and Methods: Seventy two muslim patients with acute appendicitis requiring open, emergency appendicectomies under general anaesthesia were recruited and randomised into three groups: Group A: patients who listened to prayer recitation, Group B: patients who listened to music, Group C: control group - patients who did not listen to any prayer or music. Intraoperative blood pressure, heart rate and postoperative pain scores were monitored. Results: The demographic data, pre- and post-headphones application haemodynamics were compared. There were significantly lower heart rates at 10, 20, 30, 40, 50, 60 minutes for Group A and at 50 and 60 minutes for Group B patients when compared to Group C. Significant reduction in postoperative pain scores were seen in Group A patients at 30 minutes and 8 hours as compared to Group C patients. No significant differences in pain scores were seen between Group B and C patients. No significant differences in additional analgesic requirements postoperatively were seen in all three groups. Conclusion: Listening to prayer recitation or music intraoperatively significantly lowered intraoperative heart rates, however only prayer recitation significantly reduced postoperative pain scores as compared to the control group.